Microstrip and Printed Antenna Design - Bancroft, Randy (Telecommunications Ser., 2019)
This updated third edition of this popular book covers all types of printed microstrip antenna design, from rectangular to circular, broadband and dual band, and millimeter wave microstrip antenna to microstrip arrays. The book features new analysis of rectangular and circular microstrip antenna efficiency, and surface wave phenomena.